2019
DOI: 10.1111/jrh.12400
|View full text |Cite
|
Sign up to set email alerts
|

Tracking Opioid Prescribing Metrics in Washington State (2012‐2017): Differences by County‐Level Urban‐Rural and Economic Distress Classifications

Abstract: Purpose High‐risk opioid prescribing is a critical driver of prescription opioid‐related morbidity and mortality. This study explored opioid prescribing patterns across urban‐rural and economic distress classifications. Secondarily, this study explored the urban‐rural distribution of relevant health services, economic factors, and population characteristics. Methods County‐level opioid prescribing metrics were based on quarterly Washington State Prescription Monitoring Program data (2012‐2017). Counties were c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 55 publications
0
8
0
Order By: Relevance
“…Other studies have shown that there are considerable differences in opioid-related measurements between rural and urban areas. The rural areas were found to have higher rates of opioid prescription, higher rates of high-dose opioid prescription, or fewer resources for inpatient and outpatient opioid treatment, etc., in comparison to urban areas (Keyes et al 2014 ; Sears et al 2020 ; Shoff et al 2021 ). Serdarevic et al ( 2017 ) suggest that older women, especially, those living alone, have higher rates of prescription opioid use.…”
Section: Introductionmentioning
confidence: 99%
“…Other studies have shown that there are considerable differences in opioid-related measurements between rural and urban areas. The rural areas were found to have higher rates of opioid prescription, higher rates of high-dose opioid prescription, or fewer resources for inpatient and outpatient opioid treatment, etc., in comparison to urban areas (Keyes et al 2014 ; Sears et al 2020 ; Shoff et al 2021 ). Serdarevic et al ( 2017 ) suggest that older women, especially, those living alone, have higher rates of prescription opioid use.…”
Section: Introductionmentioning
confidence: 99%
“…It is noteworthy, but not surprising, that opioid dispensing in LBBA counties was higher at baseline and remained higher throughout all time periods when compared to HBBA counties. Overall opioid prescribing rates are commonly higher in rural counties, 22 , 23 , 24 , 25 , 26 which made up 80.85% of LBBA counties versus 34.62% of HBBA counties in this study. This may be influenced by a higher prevalence of pain, specifically chronic and high‐impact chronic pain, in rural communities; 27 lower availability of other pain treatment modalities; 28 or other factors.…”
Section: Discussionmentioning
confidence: 64%
“…We used data for all persons insured with an SHI for at least 180 days in 2010 and who were 18 years or older in the respective year. On a state level, the number of all insured persons was provided by age group (18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44)(45)(46)(47)(48)(49), 50-69 and ≥70 years) and sex whereas on the district level only the overall numbers, the mean age and sex ratio per district were available.…”
Section: Data Sourcementioning
confidence: 99%
“…When exploring reasons for regional variations of opioid use, several factors come into play including (a) patients' characteristics such as demographics or burden of pain, (b) physicians' attitude or schools of thinking with respect to opioids but also (c) the health care system including access to specialized care, availability of services and the possibility of reimbursement for alternative treatments. 33 In contrast to the US where for instance prescription drug monitoring programs can be regulated via state-level policies and thereby contribute to regional variations of opioid use, opioid prescribing and dispensing in Germany is subject to national regulations.…”
Section: Potential Reasons For Regional Variationsmentioning
confidence: 99%